EDUKASI PENGELOLAAN OBAT SECARA MANDIRI DI PAROKI WARAK - Linawati, Yunita; Setiawati, Agustina; Sabatti, P. Henrietta Puji Dwi Astuti Dian (Universitas Sanata Dharma, 2024)
Self-medication is a community effort to choose treatment and medication to deal with complaints or symptoms of disease before seeking help from health facilities or medical personnel. There is a need and interest among Warak Parishioners regarding education on independent drug management at the household level because they do not yet have basic drug knowledge regarding drug categories and how to obtain, store, and dispose of drugs properly and correctly. This activity aims to provide education to people so that they are able to recognize types of medicines, how to get them, and how to store medicines properly, including regarding the period of use of medicinal preparations, and how to dispose of medicinal preparations properly and correctly. This activity is expected to improve the ability of Warak Parishioners to obtain, use, store, and dispose of medicine properly and correctly. The service activities began with attendance, distribution of goodie bags, pretest (10 minutes), education (60 minutes), question and answer (15 minutes), and posttest (10 minutes). The 38 participants consisted of the majority of women, aged 56-65 years and most of them had a high school education. The education provided could increase the knowledge of the Warak Parish community regarding independent, good, and correct medication management.